Design research in education : - Bakker, Arthur
"Design Research in Education is a practical guide containing all the information required to begin a design-research project. Providing an accessible background to the methodological approaches used in design research as well as addressing all the potential issues that early career researchers will encounter, the book uniquely helps the early career researcher to gain a full overview of design research and the practical skills needed to get their project off the ground. Based on extensive experience, the book also contains multiple examples of design research from both undergraduate and postgraduate students, to demonstrate possible projects to the reader. With easy to follow chapters and accessible question and response sections, Design Research in Education contains practical advice on a wide range of topics related to design research projects including: - The theory of design research, what it entails, and when it is suitable - The formulation of research questions - How to structure a research project - The quality of research and the methodological issues of validity and reliability - How to write up your research - The supervision of design research Through its theoretical grounding and practical advice, Design Research in Education is the ideal introduction into the field of design-based research and is essential reading for Bachelors, Masters and PhD students new to the field, as well as to supervisors overseeing projects that use design research." --